Upaya pengelolaan lingkungan hidup terhadap abrasi (studi kasus: pantai Krakal Kabupaten Gunung Kidul) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Abstract Krakal beach is the one of the beaches in GunungKidul that was visited by tourists in great numbers. But, the land erosion because of sea waves is already reduces the beach beauty. If this problem does not get the prevention soon, it is worried that the environmental damage because of land erosion which is caused by sea waves will be in serious condition. Now the effort can be done is the beach area reforestation. The purpose of this research was to_find out the alternative effort can be done to handle the land erosion because of sea waves in Krakal beach, and to analyze if the alternative efforts are already appropriate with the environmental management purpose. Besides, the other purpose of this research was to find out the proponent and obstacle factors to handle the land erosion because of sea waves. Research data was obtained through library study and field study by interviewing with the related officers. These data was analyzed qualitatively. The research shows that the alternative efforts can be done by the officers are the socialization of environmental conservation, including the socialization of Act No. 23 of 1997